Circadian control of eclosion: interaction between a central and peripheral clock in Drosophila melanogaster. - Myers, E.M.; Yu, J.; Sehgal, A. (Current Biology, 2003)
Drosophila melanogaster display overt circadian rhythms in rest:activity behavior and eclosion. These rhythms have an endogenous period of approximately 24 hr and can adjust or "entrain" to environmental inputs such as light. Circadian rhythms depend upon a functioning molecular clock that includes the core clock genes period and timeless (reviewed in and ). Although we know that a clock in the lateral neurons (LNs) of the brain controls rest:activity rhythms, the cellular basis of eclosion rhythms is less well understood. We show that the LN clock is insufficient to drive eclosion rhythms. We establish that the prothoracic gland (PG), a tissue required for fly development, contains a functional clock at the time of eclosion. This clock is required for normal eclosion rhythms. However, both the PG clock function and eclosion rhythms require the presence of LNs. In addition, we demonstrate that pigment-dispersing factor (PDF), a neuropeptide secreted from LNs, is necessary for the PG clock and eclosion rhythms. Unlike other clocks in the fly periphery, the PG is similar to mammalian peripheral oscillators because it depends upon input, including PDF, from central pacemaker cells. This is the first report of a peripheral clock necessary for a circadian event.